The role of policy in supporting environmentally sustainable foodservice in healthcare: lessons from exemplar hospitals - Carino, Stefanie; Collins, Jorja; Malekpour, Shirin; Porter, Judi (Frontiers in Nutrition, 2023)
Background Foodservice in hospitals contributes to the environmental footprint of healthcare delivery. There is little known about the role of policy in supporting environmentally sustainable foodservices. The aim of the study was to explore policy in exemplar environmentally sustainable hospital foodservices from the perspective of hospital staff, towards what makes a policy effective, the limitations of policy, and the influential levels and types of policy. Methods A generic qualitative inquiry approach was utilized. Staff involved in foodservices were interviewed about the role of policy during 2020-21 from 14 hospitals across nine countries. Data were analyzed using framework and thematic analysis. Results Policies spanned across high level policies at the level of the healthcare organization, local hospital procedures and protocols, as well as public policy from local, state/provincial and national government. Internal organizational policy was used to embed practices within the organization in the long term and help to build a shared vision and goal where public policy had lacked guidance. The creation, content and methods of communication and creating accountability made internal organizational policy successful. Public policy was most effective when it was mandatory, had clearly defined targets and funding to assist implementation. These exemplar hospitals also demonstrated attributes of policy entrepreneurs by engaging with policy makers to share their stories and lobby government for policy change. Discussion Policy from within the healthcare organization is an important mechanism for enabling hospitals to deliver and maintain environmentally sustainable foodservice. Public policy must be designed considering the unique implementation challenges hospitals face to ensure they are successful.